An improved mathematical model for predicting liquid spray and atomization characteristics - 512289 Hossam Said Mohamed Aly; Mohammad Nazri Mohd. Jaafar; Fakulti Kejuruteraan Mekanikal (2011)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2011